(untitled) (Third Sector Social Economic Review, 2023)
Every business has competition and sustainability concerns. Businesses act socially to mitigate or eliminate these concerns. Thus, beyond the laws and contracts, they adopt the principle of improving the welfare quality of their employees, customers, and society, and support local and global improvement. The execution of this process through human resources management points to socially responsible human resources management. In this research study, the desire of human resources to conduct their social responsibility actions with an employee-oriented approach is explained with the stakeholder, social system, corporate, and corporate responsibility performance theories. At this point, socially responsible human resources management assumes a crucial role in the steps to be taken so that employees, as internal stakeholders, develop a sense of belonging to their institutions, and feel loyal, productive, and valuable. In the research study, it was aimed to reveal the impact of socially responsible human resources management on individual performance. A survey questionnaire technique was used as the data collection method in the research and 201 participants were reached by employing the convenience sampling method. A quantitative approach was adopted to test the research hypothesis, and the measurement model of the research and structural analyses of the model were estimated using the SmartPLS 4.0.8.3 software. As a result of the research, it was determined that socially responsible human resources management was effective in eliminating concerns regarding employee rights, and increasing employee productivity and performance. In the study, it was revealed that socially responsible human resources management and internal stakeholders in the automotive sector, which has an important place in the global economy, are prioritized and that it is an application that creates benefits in corporate, local, and global terms. In the research study, theoretical and practical implications regarding the socially responsible human resources method as an antecedent of individual performance were included, and suggestions were made for future research studies.